Physical analyses and quimical composition of coffee submitted to different fungicidal treatments - Abrahão, Adriano Andrade; Pereira, Rosemary Gualberto Fonseca Alvarenga; Borém, Flavio Meira; Rezende, Juliana Costa de; Barbosa, Jose Carlos (Coffee Science - ISSN 1984-3909)
<!–[if gte mso 9]> Normal 0 21 false false false PT-BR X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 415 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:10.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> The objective of this work was to ascertain the influence of different fungal disease control methods for coffee (Coffea arabica L.) on the physical classification and chemical composition of coffee beans These practices were undertaken in agricultural years 2002/03 and 2003/04. A completely random design was used with subdivided plots, using repetitions in 2 x 3 factorial scheme, and two harvests and three fungicide treatments (systemic fungicide, trade name Ópera®, cupric fungicide, trade name Cobox®, and non-treated control with fungicides). The fruits were separated in parchment and floaters. The quality evaluations of the beans took place through physical and chemical analyses. The Opera® and Cobox® fungicide treatments influence the classification by type and the chemical composition of the floaters in a positive way. The Opera® fungicide provides higher results in total sugars of floaters.